Development and experimental validation of a thermoelectric test bench for laboratory lessons - Antonio Rodríguez (Journal of Technology and Science Education, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> The refrigeration process reduces the temperature of a space or a given volume while the power generation process employs a source of thermal energy to generate electrical power. Because of the importance of these two processes, training of engineers in this area is of great interest. In engineering courses it is normally studied the vapor compression and absorption refrigeration, and power generation systems such as gas turbine and steam turbine. Another type of cooling and generation less studied within the engineering curriculum, having a great interest, it is cooling and thermal generation based on Peltier and Seebeck effects. The theoretical concepts are useful, but students have difficulties understanding the physical meaning of their possible applications. Providing students with tools to test and apply the theory in real applications, will lead to a better understanding of the subject. Engineers must have strong theoretical, computational and also experimental skills. A prototype test bench has been built and experimentally validated to perform practical lessons of thermoelectric generation and refrigeration. Using this prototype students learn the most effective way of cooling systems and thermal power generation as well as basic concepts associated with thermoelectricity. It has been proven that students learn the process of data acquisition, and the technology used in thermoelectric devices. These practical lessons are implemented for a 60 people group of students in the development of subject of Thermodynamic including in the Degree in Engineering in Industrial Technologies of Public University of Navarra. <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="70" SemiHidden="false" UnhideWhenUsed="false" Name="Dark L